A family matter [large type] - Lynch, Claire, 1981- (Center Point Large Print, 2025)
"A young wife following her heart. A husband with the law on his side. Their daughter, caught in the middle. Forty years later, a family secret changes everything. 1982. Dawn is a young mother, still adjusting to life with her husband, when Hazel lights up her world like a torch in the dark. Theirs is the kind of connection that's impossible to resist, and suddenly life is more complicated, and more joyful, than Dawn ever expected. But she has responsibilities and commitments. She has a daughter. 2022. Heron has just received news from his doctor that turns everything upside down. He's an older man, stuck in the habits of a quiet existence. Telling Maggie, his only child-the person around whom his life has revolved-seems impossible. Heron can't tell her about his diagnosis, just as he can't reveal all the other secrets he's been keeping from her for so many years. A Family Matter is a heartbreaking and hopeful exploration of love and loss, intimacy and injustice, custody and care, and whether it is possible to heal from the wounds of the past in the changed world of today."--